Análise de redes de colaboração científica entre a Educação Especial e a Fonoaudiologia - Bello, Suzelei Faria (Universidade Federal de São Carlos, 2013)
The researcher is responsible as the main objective of expanding knowledge that in order to actualize it as a contribution to science must be recognized and understood by other scientists. Thus, the possibility of shared work and adds value to the integrated object searched. Given this, reflect on Special Education and Speech interface becomes important compared to the current context of joint work and collaboration that pervades the scientific world. Thus, this research aimed to identify the theoretical frameworks used by the authors of dissertations and theses in the Graduate Program in Special Education, Federal University of São Carlos (PPGEs/UFSCar), interface and Special Education Speech during the years 1981 to 2009, and to analyze the scientific collaboration networks formed in the publication of books, book chapters and articles that characterize the interface. The research proposal was kind of investigative documentary with an exploratory-descriptive way. We used two different methods: a bibliometric analysis and social network analysis. In bibliometric analysis, data were extracted from 96 studies components of the interface screen (78 dissertations and theses 18). Moreover, the analysis of scientific collaboration networks, data were extracted from the Lattes platform of Lattes from 73 authors that have characterized the interface, selection was focused on three formats: book publishing, book chapters and articles. As a preliminary result we can observe that the networks of collaboration showed distinct characteristics in the three formats of publications, especially in the form of books that the networks formed by the authors found themselves disconnected because the formats of book chapters and articles, there collaboration to occur among different authors with different trait. However, the themes that developed were the most frequently targeted for the hearing impaired, wrapped in greater inter-institutional relations between university degree UFSCar, USP and UEL. It is hoped that the analysis of the collaborative networks can contribute as facilitator and promoter of research, so that the interface is strengthened and the relationship between the two sciences pervade other subjects, also important for the growth of both areas.
Keywords: Educação especial; Análise de redes; Análise bibliométrica; Colaboração científica; Fonoaudiologia; Bibliometria; Análise de colaboração; Special education; Speech-language pathology; Bibliometrics; Analysis collaboration; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL